From clientelist arrangements to the sovereign debt crisis: The social and spatial impact in Athens - Μαλούτας Θωμάς (The Greek Review of Social Research, 2011)
Following a brief reference to the impact of globalization and economic restructuring on urban social structures, the paper deals with the impact of the Greek sovereign debt crisis on the socio-spatial structure of Athens. The discussion focuses on the rather weak polarization and segregation effects result ing from global forces until the mid 2000s, and on the subsequent change of socioeconomic and demographic conditions forming a new socioeconomic and political environment, in which the socially dividing impact of the current crisis is expected to be particularly negative.